IMPACT OF CREDIT RISK AND CAPITAL ADEQUACY ON ISLAMIC AND CONVENTIONAL BANKING HEDGING - siddiq, Abbokar; Gamal, Ebrahim Al (International Journal of Research -GRANTHAALAYAH, 2020)
This study aims to examine the relationship between credit risk and capital adequacy with the banking hedging of Islamic and conventional banks in Yemen. A sample of 4 conventional banks and 3 Islamic banks was used during (2012-2017). Using Pearson correlation and regression analysis, the study concludes that there is a statistically significant relationship between credit risk and banking hedging and a strong statistically significant relationship between capital adequacy and banking hedging. Based on the type of bank, results indicate a negative relationship but no statistical significance between conventional banks' credit risk and banking hedging. There is a statistically significant relationship between credit risk and banking hedging of Islamic banks. Capital adequacy positively interacts with the banking hedging in both banks.